Evidências de validade do Teste de Zulliger em idosos com doença renal crônica - Gregoleti, Viviane (2015)
Nowadays it is possible to observe that, although there is a progressive increase in the elderly population with chronic diseases, the research validity of self-expression techniques with these individuals are almost nonexistent. Therefore, the present work aimed to verify the validity of Zulliger test in the evaluation of hemodialysis in elderly. Notably, the scientific composition, original from the thesis entitled "The Zulliger Test in Elderly patients on Hemodialysis and the Relationship between External Variables" aimed to demonstrate the validity of Zulliger to identify cognitive and interpersonal relationship in elderly patients with CKD and check the relationship between external variables. Participants composed two groups, namely a group of 30 elderly on hemodialysis, called clinical group (CG) and another group of 30 elder free of the disease, entitled non-clinical group (CNG). As instruments it were used the Mini Mental State Examination (MMSE), the socio-demographic and health protocol and the Zulliger test in the Comprehensive System (ZCS). Data from the sociodemographic and health protocol and structural summary from ZSC were exported to a database file on Statistical Package for Social Sciences - SPSS, version 22.0, for statistical analysis. First, it was performed descriptive statistics of the variables age, education and marital status of both groups and then the results were compared. In the sequel, to evaluate the differences between the cognitive triad and the interpersonal relationship between the two groups we used the Mann Whitney U test, and to scale the size of the effect was the d of Cohen. Associations between DRC and external variables studied were made through Spearman correlation coefficient. It was considered as statistically significant value tests p < 0.05. The results showed that the GC showed lowering of variables Xu% (p=0.031, d=0.58), R (p=0.002, d=0.78), Fd (p=0.021, d=0.65) and isolation (p=0.006, d=0.61), elevated X-% scores, and PHR>GHR. There was a positive association between time of diagnosis and family support (p=0.043), and education (p=0.045). Older people with CKD presented therefore, decrease in productivity, cognitive and interpersonal relationship problems hindered when compared to GNC. These results confirm the relevance of ZCS as a with valid tool for understanding elderly with CKD and show the family support and the level of education as important external factors for mental health